Performing Whiteness, Troubling Blackness: Afropolitanism and the Visual Politics of Black Bodies in YouTube Videos - (:unkn) unknown (My University, 2021)
his article explores the relation between linguistic and nonlinguistic signs in enregisterment processes (Agha 2007) through the analysis of multimodal images of racial otherness in YouTube videos. It aims to show the role of images in indexing social meaning and performing hegemonic Whiteness among metropolitan Cameroonian-French elites living in Paris, through the use of a specific semiotic register indexing an “Afropolitan” persona – an elite, socially mobile and transnational type of Blackness. By focusing on the poiesis of “image-texts” (Nakassis 2019), this article will contribute to understanding the “total semiotic fact”of racial and social differentiation. It will also demonstrate that these images constitute a counter-discourse and are political acts that negotiate agency and contest power relations.
Keywords: African Research